Sub-Classification of Cirrhosis Affects Surgical Outcomes for Early Hepatocellular Carcinoma Independent of Portal Hypertension - Zhang, Er-lei; Li, Jiang; Li, Jian; Wang, Wen-qiang; Gu, Jin; Huang, Zhi-yong (Frontiers in Oncology, 2021)
Severity of liver cirrhosis is distinct from significant clinical portal hypertension because there exist different degrees of liver cirrhosis in hepatocellular carcinoma (HCC) patients without significant clinical portal hypertension. Whether severity of cirrhosis affects surgical outcomes for HCC patients in absence of portal hypertension or not remains unclear. This study aims to analyze the effect of cirrhotic severity on surgical outcomes for HCC patients with hepatitis B virus (HBV) infection in absence of portal hypertension. This retrospective study enrolled consecutive 166 patients who underwent curative resection for a single HCC≤5 cm in absence of portal hypertension between February 2011 and December 2013. Liver cirrhosis was sub-classified into no/mild (no/F4A) and moderate/severe (F4B/F4C) according to the Laennec scoring system. The surgical outcomes and complications were analyzed. There was no treatment-related hospital mortality in this study. Major complications were significantly more frequent in the F4B/F4C group than in the no/F4A group (17.0% vs 7.4%, p<0.001). The 1-year, 3-year and 5-year overall survival (OS) rates were 98.5%, 88.1% and 80%, respectively, in the no/F4A group, which were significantly higher than those in the F4B/F4C group (98.0%, 69.2% and 54.7%, p=0.001). Microscopic vascular invasion, absence of tumor capsule and severity of liver cirrhosis were independent risk factors of surgical outcomes for HCC patients without portal hypertension. Severity of liver cirrhosis affects surgical outcomes of early-stage HCC patients independent of portal hypertension.